Oesophageal propulsive force and its relation to manometric pressure. Issue 6 (June 1992) - Russell, C O; Bright, N; Buthpitiya, G; Alexander, L; Walton, C; Whelan, G
Abstract : A fixed volume capsule incorporating a force transducer and a side hole for manometric measurements was constructed and calibrated. Simultaneous measurements of the propulsive (aboral) force and the manometric pressure (intraluminal pressure) were made at 5, 10, and 15 cm above the lower oesophageal sphincter and in response to dry and wet (5, 10, and 15 ml) swallows. The propulsive force and manometric pressure waves had a simultaneous onset and were of similar duration. Peak values of propulsive force for wet swallows increased significantly as measurements were made progressively more distally within the oesophagus and were greatest in the distal oesophagus. The association between manometric pressure and propulsive force is not strong (r = 0.61) suggesting that intraluminal pressure is a poor predictor of propulsive force and hence an unreliable measure of oesophageal 'function'.